2021
DOI: 10.3389/fsufs.2021.671419
|View full text |Cite
|
Sign up to set email alerts
|

Role of Climate-Smart Agriculture in Enhancing Farmers' Livelihoods and Sustainable Forest Management: A Case of Villages Around Songe-Bokwa Forest, Kilindi District, Tanzania

Abstract: Climate change and variability are happening in Tanzania, and their impacts are felt in the socioeconomic sectors, as they have resulted in the decline of agricultural productivity and increased deforestation. This study assessed the actual changes in deforestation levels and improved livelihoods caused by the adoption of climate-smart agriculture (CSA) practices. Data were collected through semi-structured household questionnaires, focus group discussions, key informants, GIS tools, and observations. Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A similar result was reported in a study in Bihar [6]. The problem of lack of interest in cultivation due to poor return in short term and poor education level of the farmers also a reason of non adoption of CSALT [7]. Similar problems were also reported from in Kashmir valley [8].…”
Section: Resultssupporting
confidence: 83%
“…A similar result was reported in a study in Bihar [6]. The problem of lack of interest in cultivation due to poor return in short term and poor education level of the farmers also a reason of non adoption of CSALT [7]. Similar problems were also reported from in Kashmir valley [8].…”
Section: Resultssupporting
confidence: 83%
“…A case of Villages Around Songe-Bokwa Forest, Kilindi District, Tanzania [22] revealed that there was rainfall variability, shift in rainfall patterns, and increase in temperature in the study area. Figure 3 shows impacts of climate change on household livelihoods, showing that 38.7, 18.6, and 12.8% of households perceived that climate change variability (CCV) resulted in food shortage, decreased income, increased disease outbreaks, youth emigration, and rise of food price.…”
Section: Economic and Environmental Benefits Of Application Csgmentioning
confidence: 92%
“…Climate-smart agriculture fulfills the need for an agricultural system that encourages climate change mitigation and adaptation activities, while enhancing food security (FAO, 2013;Neufeldt et al, 2013). It enhances productivity and incomes while mitigating forest degradation, adjusting to climate changes, and reducing greenhouse gas (GHG) emissions in situations where possible (Nkumulwa and Pauline, 2021). Site-specific CSA practices benefit users while safeguarding natural resources.…”
Section: Potential Benefits Of Csa Practicesmentioning
confidence: 99%